2008
DOI: 10.1111/j.1095-8649.2008.01880.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding strategy of the megamouth shark Megachasma pelagios (Lamniformes: Megachasmidae)

Abstract: The feeding biology of the planktivorous megamouth shark Megachasma pelagios was investigated. Morphological examination disclosed that the megamouth has a suite of unique characteristics among sharks, such as large mouth, large bucco-pharyngeal cavity, elongate jaw cartilages, long palatoquadrate levator and preorbital muscles, long ethmopalatine ligament and elastic skin around the pharynx. The combination of these characters suggests that the megamouth shark performs engulfment feeding that is typically see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 10 publications
3
36
0
1
Order By: Relevance
“…These large gills would not be necessary in pump suspension-or engulfmentfeeding fishes, which filter by first creating a suction force to entrain zooplankton-rich water and then subsequently close their mouths to force this water over the gill rakers. This point is illustrated nicely by comparing the smaller gill morphology of a megamouth shark, Megachasma pelagios, which has been hypothesized to use an engulfment feeding strategy (Nakaya et al, 2008), with that of the large-gilled basking sharks (Bigelow and Schroeder, 1953) and whale sharks (Colman, 1997), which use, at least in part, ram suspension feeding. Though we had predicted that ram filtration efficiency would increase with gill size, we did not predict that the particle distribution would shift to that of a planktonic specialist without having to adjust the pore size of the filter.…”
Section: Discussionmentioning
confidence: 99%
“…These large gills would not be necessary in pump suspension-or engulfmentfeeding fishes, which filter by first creating a suction force to entrain zooplankton-rich water and then subsequently close their mouths to force this water over the gill rakers. This point is illustrated nicely by comparing the smaller gill morphology of a megamouth shark, Megachasma pelagios, which has been hypothesized to use an engulfment feeding strategy (Nakaya et al, 2008), with that of the large-gilled basking sharks (Bigelow and Schroeder, 1953) and whale sharks (Colman, 1997), which use, at least in part, ram suspension feeding. Though we had predicted that ram filtration efficiency would increase with gill size, we did not predict that the particle distribution would shift to that of a planktonic specialist without having to adjust the pore size of the filter.…”
Section: Discussionmentioning
confidence: 99%
“…Those swarms formed at the surface in daytime. Nakaya et al (2008) suggested that the megamouth shark performs engulfment feeding like a rorqual whale, and is morphologically distinguished from a basking shark and a whale shark in the buccal structure which is composed of a larger bucco-pharyngeal cavity and stretchable skin on the ventral and lateral sides of the head in the megamouth shark. The present results on stomach contents and previous information suggest that the megamouth specimen was caught soon after feeding on a surface swarm of E. pacifica.…”
mentioning
confidence: 99%
“…With each scenario presented here, once a desired level of electrosensory stimuli has been achieved, ingestion of prey would then follow using a gulp-and suction-feeding mechanism (Nakaya et al 2008) to consume all the available planktonic prey in the vicinity of the head, thereby maximising the efficiency of each feeding event.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other planktivorous sharks such as Cetorhinus maximus (basking shark) and Rhincodon typus (whale shark), M. pelagios is thought to adopt a unique method of filter feeding. Instead of swimming continuously with its enormous mouth wide open, filtering water for plankton and jellyfish, M. pelagios is thought to attract prey with a bioluminescent strip along its upper jaw (Taylor et al 1983) -although this has not yet been supported with histological evidence (Nakaya et al 2008) -and then engulf it in a single motion, similar to the feeding mechanism of some baleen whales (Compagno 1990, Nakaya et al 2008). This active method of ingesting prey is thought to be due to the restricted internal gill openings and jaw morphology of M. pelagios sharks (Compagno 1990, Nakaya et al 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation